Tapestries for the courts of Federico II, Ercole, and Ferrante Gonzaga 1522 - 63 - Brown, Clifford M. 1937-2012; Delmarcel, Guy 1941- (Univ. of Washington Press, 1996)
Clifford M. Brown has exhaustively researched archival material in Mantua and Parma in order to document the tapestries commissioned for or purchased by the sons of Francesco II Gonzaga and Isabella d'Este
Keywords: Gonzaga (Famille) - Mécénat; Gonzaga (Family) - Art patronage; Gonzaga family -- Art patronage; Gonzaga -- Familie; Geschichte 1522-1563; Particuliere verzamelingen; Tapisserie de la Renaissance - Belgique - Bruxelles; Tapisserie de la Renaissance - Flandre; Wandtapijten; Tapestry -- Belgium -- Brussels; Tapestry -- Flanders; Tapestry, Renaissance -- Belgium -- Brussels; Tapestry, Renaissance -- Flanders; Bildteppich; Textilkunst; Renaissance; Malerei; Vorlage; Belgien; Oberitalien; Brüssel